Biochemical properties and potential application of proteases from alkalophilic bacillus lehensis G1 - Sulaiman N.A.; Mahadi N.M.; Nur Zazarina Ramly (Penerbit Universiti Sains Malaysia, 2024)
Indexed by WOS/ Scopus